Regional Innovation System in Rural Economic Institutional: Empirical Evidence From Semarang, Indonesia - Edy Dwi Kurniati; Indah Susilowati; S. Suharno (Muhammadiyah University Press, 2019)
This study aims to analyze the factors that influence the innovation capacity of the rural economic institution and its impact on institutional performance.Research was conducted by interviewing 111 managers of rural economic institutions in Semarang regency, Indonesia. Factors of policy and regulation, development of innovation infrastructure, assistance and integration of knowledge were used to analyze the role of the Government and Higher Education in the village innovation system. The institutional management and innovation culture capacity factors were used to analyze the role of rural economic institutions. Policy and regulatory factors, innovation infrastructure, management capacity, assistance capacity, innovation culture and knowledge integration were measured based on the preference of the rural economic institution manager. The qualitative model was examined through an empirical analysis to fulfill the proposed aim of the research.The results of the study showed that: the influential factors on the innovation capacity in rural areas were policy and regulation support, innovation infrastructure, management capacity, innovation culture and knowledge management. Innovation Capacity had a positive impact on institutional performance.The implication of this study highlighted the importance of strengthening institutional and knowledge-based rural economic organizations which was integrated among stakeholders as actors in the rural innovation system.